PNI versus SCI: the acute neuronal-specific transcriptional responses after lesion - Correia, Patrícia D. (2020)
Spinal cord injury (SCI) has devastating functional consequences to patients, but lacks effective treatment. Peripheral nerve injury (PNI) is a widely used model to discover new regeneration associated genes (RAGs). Various transcriptomic studies have profiled injured spinal cord or sciatic nerve tissues aiming to discover new RAGs. However, it is difficult to depict neuronal-specific responses from whole-tissue analyses. Since the first hours after injury are extremely important to trigger a regenerative program, we started investigating the early differential transcriptomic alterations in affected peripheral and central neurons 24 hours after PNI or SCI. Laser Capture Microdissection was used to dissect rat Dorsal Root Ganglia (DRG) and motor neurons after PNI, and DRG and pyramidal cortex neurons after SCI. RNA sequencing was then used to provide insight into the transcriptome of the dissected neuronal populations and to search for highly relevant transcripts. Our preliminary data shows that the mRNA regulation is more robust in DRG neurons after PNI than after SCI. Also, DRG neurons' response after SCI was more pronounced than the one of pyramidal neurons. Gene enrichment analysis revealed that protein metabolism and cytoskeleton organization pathways are some of the most regulated pathways in DRG neurons after PNI, while after SCI, laminin-binding and steroids maturation pathways are altered. This study allows to identify the most relevant pathways regulated in the acute phase of SCI and PNI. Overall, these results may help to develop therapeutic strategies that stimulate regeneration and repair after SCI or other CNS-affecting pathologies.